Testing Communicative Competence and Performance in UMSEP - Khong, Chooi Peng; Rajagopal, Subramaniam (Journal of Modern Languages, 2017)
This paper describes how UMSEP attempts to redress the imbalance in designing a testing programme and a set of testing procedures that mirror the philosophy behind the approach adopted in the materials that have been developed in the study. The paper reveals that a valid testing programme should reflect the course aims and content.